A RELATIONSHIP BETWEEN KNOWLEDGE INSPIRATION, LANGUAGE PROFICIENCY AND LESSONABILITY - Despita Despita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study is expected to discover: (1) There is a relationship between of knowledge inspiration and language proficiency; (2) There is a relationship between language proficiency and lesson ability and (3) There is a relationship between knowledge inspiration, language proficiency and lesson ability. The study is directed by January – April 2019 in the second semester understudies, scholastic year 2018-2019. The information of the exploration is gathered utilizing survey to gather the information of understudies' knowledge inspiration and experiment to gather the information of language proficiency and lesson ability. The data are then being explored utilizing basic connection and various straight relapse. The study discoveries show that (1) There is a positive relationship in the midst of knowledge inspiration and language proficiency (ry1 = 0.745> r table = 0.205); (2) There is critical positive relationship between language proficiency and lesson ability (0.720 > 0.205; (3) There is a positive relationship between knowledge inspiration, language proficiency and lesson ability (F perception 91.941 > F table 3.11).